Post-intubation tracheal injury during esophagectomy - Adhikari , Mahesh Mani; Thakur, Binay; Shun, Zhenqing; Khatiwada, Sagar; Shrestha, Shashank; Kharel, Ashish; Bhattarai, Sachee (Nepalese Journal of Cancer, 2024)
Post-intubation tracheal injuries are rare complications with serious consequences. Several factors increase the risk of tracheal injuries which may be attributed to patient, or procedure related. Majority of the tracheal injuries are managed surgically, however, role of less invasive and conservative treatment are also emerging. Case: we report a case of an elderly lady who underwent minimally invasive esophagectomy for esophageal carcinoma. She developed significant surgical emphysema within hours after surgery and massive air leak through underwater seal chest drainage tube. She was taken for emergency re-exploration. On table bronchoscopy confirmed 5 cm longitudinal tear of membranous part of cervical and upper thoracic trachea. Thoracoscopic repair along with transcervical-transtracheal repair of membranous wall of trachea and a tracheostomy was performed. She made significant recovery with few complications which were managed successfully.